Cho \(\hept{\begin{cases}a\cdot\left(b^{2+c^2}\right)+b\cdot\left(b^2+c^2\right)+c\left(a^2+b^2\right)+2abc=0\\a^{3+}b^3+c^3=1\end{cases}Tính}A=\frac{1}{a^{2017}}+\frac{1}{b^{2017}}+\frac{1}{c^{2017}}\left(a,b,c#0\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\frac{15\left(x-y\right)^5}{5\left(x-y\right)^3}-\frac{10\left(x-y\right)^4}{5\left(x-y\right)^3}+\frac{20\left(x-y\right)^3}{5\left(x-y\right)^3}\)
\(=3\left(x-y\right)^5-2\left(x-y\right)^4+4\left(x-y\right)^3\)
\(x^2+4x+3\)
<=>\(x^2+3x+x+3\)
<=>\(\left(x^2+3x\right)+\left(x+3\right)\)
<=>\(x\left(x+3\right)+\left(x+3\right)\)
<=>\(\left(x+3\right)\left(x+1\right)\)
\(c>\)\(x^2-x-12\)
<=>\(x^2+3x-4x-12\)
<=> \(\left(x^2+3x\right)-\left(4x-12\right)\)
<=>\(\left(x^2+3x\right)-\left(4x+12\right)\)
<=>\(x\left(x+3\right)-4\left(x+3\right)\)
<=>\(\left(x+3\right)\left(x-4\right)\)
a) \(x^2+4x+3\)
\(=x^2+x+3x+3\)
\(=x\left(x+1\right)+3\left(x+1\right)\)
\(=\left(x+1\right)\left(x+3\right)\)
b) \(x^2-4x+3\)
\(=x^2-3x-x+3\)
\(=x\left(x-3\right)-\left(x-3\right)\)
\(=\left(x-3\right)\left(x-1\right)\)
c) \(x^2-x-12\)
\(=x^2-4x+3x-12\)
\(=x\left(x-4\right)+3\left(x-4\right)\)
\(=\left(x-4\right)\left(x+3\right)\)
\(\left(x-3\right)\left(x-4\right)=\left(x-5\right)^2\)
\(\Leftrightarrow\left(x-3\right)\left(x-4\right)-\left(x-5\right)^2=0\)
\(\Leftrightarrow x^2-4x-3x+12-\left(x^2-10x+25\right)=0\)
\(\Leftrightarrow x^2-4x-3x+12-x^2+10x-25=0\)
\(\Rightarrow3x-13=0\)
\(\Rightarrow3x=13\)
\(\Rightarrow x=\frac{13}{3}\)
Cái thứ 2 là b. (a^2+c^2) đúng ko bạn
đúng rồi nha